2024
DOI: 10.3390/separations11010035
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Deep Eutectic Solvents in the Extraction of Organic Compounds from Food Industry By-Products and Agro-Industrial Waste

Maja Molnar,
Dajana Gašo-Sokač,
Mario Komar
et al.

Abstract: Global food waste has a huge impact on the environment, as it is a source of greenhouse gas emissions and wasted natural resources. Across the world, over 30% of food is lost or wasted each year. Aside from this, the food industry, as well, is one of the biggest sources of agro-industrial waste and by-products, which can be valorized and used for different purposes. Such waste is a good source of bioactive organic compounds that can be extracted without altering their properties, where deep eutectic solvents c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 204 publications
(200 reference statements)
0
4
0
Order By: Relevance
“…Regardless of the many advantages of DES, some recovery issues of the dissolved solutes after extraction have been reported such as solvent distillation but techniques are being explored: use of macroporous resins, solid phase extraction (SPE), antisolvent method and back extraction (Molnar et al, 2024), as shown in Figure 4, however, these methodologies still require the use of organic solvents such as ethanol and methanol (Palos-Hernández et al, 2022). However, the most recent techniques in protein extraction and purification involve the use of DES (Lin et al, 2022;Karimi et al, 2024); processes based on these solvents have reported higher extraction efficiencies up to 62-90% for plant proteins and aminoacids, higher results than other techniques, such as acid-based method (Li et al, 2021;Bowen et al, 2022;Zhou et al, 2022).…”
Section: Protein Extraction and Purification With Desmentioning
confidence: 99%
See 2 more Smart Citations
“…Regardless of the many advantages of DES, some recovery issues of the dissolved solutes after extraction have been reported such as solvent distillation but techniques are being explored: use of macroporous resins, solid phase extraction (SPE), antisolvent method and back extraction (Molnar et al, 2024), as shown in Figure 4, however, these methodologies still require the use of organic solvents such as ethanol and methanol (Palos-Hernández et al, 2022). However, the most recent techniques in protein extraction and purification involve the use of DES (Lin et al, 2022;Karimi et al, 2024); processes based on these solvents have reported higher extraction efficiencies up to 62-90% for plant proteins and aminoacids, higher results than other techniques, such as acid-based method (Li et al, 2021;Bowen et al, 2022;Zhou et al, 2022).…”
Section: Protein Extraction and Purification With Desmentioning
confidence: 99%
“…The term "eutectic" is derived from the greek word meaning low melting point and can be applied for different systems like alloys and also in liquid medium (Liu et al, 2018). In recent decades, DES have been used as unconventional solvents and they can be defined as "Mixtures of two or more pure compounds for which the eutectic point temperature is lower than that of an ideal liquid mixture, presenting significant negative deviations from ideality" and, due to their multiple properties, they have been used for the extraction of bioactive compounds, stabilization of biomolecules, enhancers of drug delivery, as well as, for the treatment of food industry waste (Molnar et al, 2024). The advantage of DES consists in their simple and inexpensive preparation, which involves only mixing and stirring at temperature below 150°C (Botelho Junior et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of analytical chemistry processes, other characteristics stand out, including a broad range of solubility, tunable properties through the adjustment of the components and their molar ratios, offering a customizable platform for specific applications, and great thermal stability. Thus, it has been widely demonstrated in several publications that they possess great potential as extraction agents [18][19][20][21]. Nevertheless, its high viscosity, although effective in avoiding processes such as oxidation or degradation of certain compounds, hinders its fluidic properties, handling, and mass transfer between sample and solvent.…”
Section: Introductionmentioning
confidence: 99%